Discordant uptake of Tl-201 and Tc-99m MIBI in a patient with follicular adenoma - (:unkn) unknown (JAPANESE SOCIETY NUCLEAR MEDICINE, 2000)
Two phase Tl-201 and Tc-99m MIBI thyroid scintigraphies were carried out in a 30-year-old woman who had a solitary cold thyroid nodule seen on a pertechnetate scan. Although an early Tl-201 thyroid image showed intense uptake in the nodule, Tc-99m MIBI demonstrated a hypoactive lesion on the early image. Delayed thyroid scans showed faster washout from the nodule compared to normal thyroid tissue for both Tl-201 and Tc-99m MIBI. Later on, the patient was operated on and the nodule was found to be a follicular adenoma by histopathological diagnosis.
Keywords: Tl-201; Tc-99m MIBI; thyroid nodule; ASPIRATION BIOPSY; THYROID-NODULES; SCINTIGRAPHY; TECHNETIUM-99M-SESTAMIBI; BENIGN; LESIONS